A necessidade da periodização para uma (re)leitura dos romances The adventures of Tom Sawyer (1876) e The adventures of Huckleberry Finn (1885), de Mark Twain - Barbizan, Eduardo Alves de Deus (Universidade Federal de São Carlos, 2018)
The aim of this research is to point to the need for periodization (JAMESON, 1992) of Mark Twain's novels The Adventures of Tom Sawyer (1876) and The Adventures of Huckleberry Finn (1885) to revisit the contemporary reception of books, marked in these readings by the possible accusations of racism and prejudice made to works by critics. The objective of that thesis is to reintegrate the literary texts in their production context and investigate how the ethnic and racial issues are figured in these Twain's novels. By means of concepts of Reception Theory as proposed by Jauss (1967), especially those of horizon of expectations, synchronic and diachronic reception amplified by the political reading as presented by Fredric Jameson (1992), Antonio Candido (1970) and Roberto Schwarz (1987) will seek to re-read these novels tied to their historical context of production.
Keywords: Mark Twain; Literatura Norte-Americana; Literatura infantil; Leitura Política; Mark Twain; North American Literature; Children's literature; Political reading; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUAS ESTRANGEIRAS MODERNAS